2022
DOI: 10.1007/s12265-022-10288-z
|View full text |Cite|
|
Sign up to set email alerts
|

LINC01013 Is a Determinant of Fibroblast Activation and Encodes a Novel Fibroblast-Activating Micropeptide

Abstract: Myocardial fibrosis confers an almost threefold mortality risk in heart disease. There are no prognostic therapies and novel therapeutic targets are needed. Many thousands of unannotated small open reading frames (smORFs) have been identified across the genome with potential to produce micropeptides (< 100 amino acids). We sought to investigate the role of smORFs in myocardial fibroblast activation.Analysis of human cardiac atrial fibroblasts (HCFs) stimulated with profibrotic TGFβ1 using RNA sequencing (RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, overexpression of LINC01013ORF induced markers of fibroblast activation to the same level as observed with TGF-β1 stimulation. Although the exact mechanism by which this micropeptide affects fibrosis has yet to be elucidated, its localization suggests that mitochondrial metabolism may play a role [97]. In addition, Chingnon et al reported that LINC01013 may induce calcification of the aortic valve via the TGF-β/CCN2/CTGF axis [98].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…However, overexpression of LINC01013ORF induced markers of fibroblast activation to the same level as observed with TGF-β1 stimulation. Although the exact mechanism by which this micropeptide affects fibrosis has yet to be elucidated, its localization suggests that mitochondrial metabolism may play a role [97]. In addition, Chingnon et al reported that LINC01013 may induce calcification of the aortic valve via the TGF-β/CCN2/CTGF axis [98].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Nevertheless, the advent of transcriptomic technologies, particularly those that can resolve single cells or spatial positioning, has revealed additional layers of complexity to myofibroblast identity, reinforcing the degree to which our understanding of these paradigms has been oversimplified and incomplete 1, 2 . A recent pair of reports identified the long noncoding RNA LINC01013 , sometimes referred to as AERRIE , as a positive regulator of myofibroblast differentiation in human valvular interstitial cells 3 and human cardiac fibroblasts 4 . These effects are purported to occur through direct potentiation of CCN2 expression by the lncRNA 3 , and/or through encoding translation of a pro-fibrotic micropeptide 4 .…”
Section: Letter Bodymentioning
confidence: 99%
“…A recent pair of reports identified the long noncoding RNA LINC01013 , sometimes referred to as AERRIE , as a positive regulator of myofibroblast differentiation in human valvular interstitial cells 3 and human cardiac fibroblasts 4 . These effects are purported to occur through direct potentiation of CCN2 expression by the lncRNA 3 , and/or through encoding translation of a pro-fibrotic micropeptide 4 . Since the presence and roles of myofibroblasts are somewhat conserved among fibrotic diseases of different tissues 5 , we hypothesized that LINC01013 might be overexpressed in human dermal myofibroblasts as well.…”
Section: Letter Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Some ncRNAs possess small open reading frames (smORFs) that encode small proteins of less than 100 amino acids ( 7 , 8 ). LINC01013 , a type of long intergenic ncRNA (lncRNA), contains smORF, and micropeptide translated from it was reported to activate myocardial fibroblasts ( 9 ). It was also reported that smORFs are also present in pri-miRNAs, which are precursors of microRNAs (miRNAs), and that smORFs regulate their expression levels in pri-miR-155 and pri-miR-497 ( 10 ).…”
mentioning
confidence: 99%